Catur pusat pendidikan : The legacy of Siti Walidah in modern Islamic gender discourse - Annisa Rahmania Azis; Achmad Zaini (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
This study explores Siti Walidah's contribution to shaping the education paradigm based on the Catur Pusat Pendidikan and its relevance to modern Islamic gender discourse. The topic highlights the critical role of women in achieving gender equality, addressing challenges like unequal education access and entrenched gender stereotypes. Using a library research method with descriptive-qualitative analysis, the study finds that the Catur Pusat Pendidikan promotes quality education for women and empowers them to engage actively in social and political spheres. However, challenges such as gender bias and limited infrastructure hinder its implementation. Despite these obstacles, significant prospects for progress exist, particularly through technology and multi-stakeholder collaboration. The study underscores the importance of inclusive, high-quality education for women and advocates for sustained efforts to transform traditional gender paradigms. Recommendations include expanding educational access in remote areas and equipping women with digital skills to enhance their participation in the modern era.